Combination CT and MRI shoulder arthrography: a novel technique and improved patient journey. Issue 10 (October 2022) - Armstrong, T.; Henderson, D.J.; Entwistle, I.; Iball, G.; Rowbotham, E.
Highlights: Single injection technique for acquisition of CT and MR arthrography. Fluoroscopic CT produces diagnostic images at reduced radiation dose. Single injection double procedure has benefited patients during COVID-19 pandemic.